(untitled) (Research, Society and Development, 2020)
Gestational Diabetes Mellitus is a condition characterized by an increase in blood glucose levels, which can be initiated or diagnosed during pregnancy. This process occurs due to the production of high levels of hormones by the placenta, most of which are harmful to the action of insulin in the cells increasing the blood sugar level and can affect the growth and well-being of the fetus. Among the drugs used, Metformin Hydrochloride is an oral hypoglycemic drug used to treat Diabetes Mellitus. The present study aimed to elaborate a systematic review on the use of metformin hydrochloride in the treatment of gestational diabetes mellitus. The searches were carried out in the SciElo and Google Acadêmico databases. 763 articles were found in the initial research and after the analysis of the pre-analytical phases, only 6 were selected, since they met the inclusion criteria. After extracting the data, a relationship was made between the use of metformin with the various forms of therapy used in the studies and it was shown that metformin is a drug well applied as monotherapy, being used by 40 % of individuals in one of the studies analyzed and it is also well accepted in combination therapy with insulin in patients who have resistance to it, due to metformin being a drug with easy access and easy dosage. It is concluded that metformin is a safe, effective, low-cost and widely accepted drug for pregnant women who use it in the treatment of gestational Diabetes Mellitus.